Exploration of antibacterial metabolites producing marine bacteria from Sundarbans, Bangladesh - Sarker, Ashish Kumar; Haque, Md Anwarul; Islam, Mohammad Sayful; Rahman, Md Ajijur; Islam, Md Anwar Ul (Bangladesh Pharmaceutical Journal, 2015)
To combat the increasing numbers of antibiotic resistant strains of pathogenic bacteria new source of antibacterial agents are desperately needed. This study was aimed to discover new marine bacteria having antibacterial activity from marine soil samples of Sundarbans, Bangladesh. Using starch-casein-nitrate-agar medium thirty nine marine bacteria colonies were isolated as pure isolates from nine marine soil samples. Each of the isolates was preserved in both short term and long term basis. Based on the aerial and substrate mycelia color of the isolates they were grouped into five color series and were screened for their antibacterial activity against a series of test bacteria. Among thirty nine pure isolates twenty four isolates (61.5%) exhibited moderate to high activity against three grampositive and four gram-negative bacteria. This is due to the antibacterial metabolites secreted in the medium by most of the isolates. It suggested that Sundarbans may be an interesting, valuable and potential source for the exploration of novel marine bacteria with the potential to yield useful new antibacterial secondary metabolites of pharmaceutical interest. Bangladesh Pharmaceutical Journal 18(1): 53-60, 2015